Academic Flying and the Means of Communication - Bjørkdahl, Kristian; Franco Duharte, Adrian Santiago (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book shines a light on how and why academic work became entwined with air travel, and what can be done to change academia's flying habit. The starting point of the book is that flying is only one means of scholarly communication among many, and that the state of the planet now obliges us to shift to other means. How can the academic-as-globetrotter become a thing of the past? The chapters in this book respond to this call in three steps. It documents the consequences of academic flying, it investigates the issue of why academics fly, and it begins an effort to think through what can replace flying, and how. Finally, it confronts scholars and scientists, students, activists, research funders, university administrators, and others, with a call to translate this research into action. Kristian Bjørkdahl is a rhetoric scholar at the University of Oslo. He currently does research on the organization of science communication work, and on how the idea of Nordic colonial innocence is used rhetorically. He has been editor or co-editor of several volumes, including Pandemics, Publics, and Politics (Palgrave, 2019). Adrian Santiago Franco Duharte is a lawyer pursuing postgraduate study at the University of Oslo. He has experience from public-private partnerships, social and environmental dispute resolution, and infrastructure projects. He is currently conducting research on the role of social media communication in environmental disasters.